The Effects of Leverage, Investment Decision, Dividend Policy and Profitability, on Firm Value of the Automotive Sector Companies - Heri Ispriyahadi; Grace Aprilia Uli Putri (President University Press, 2021)
This paper examined the impact of leverage, investment decision, dividend policy and profitability on the firm value of the automotive sector companies from 2010 - 2016. There are 12 firms chosen using a purposive sampling technique implementing specific criteria. Those firms are publicly listed on the Indonesia Stock Exchange. Panel data regression (Pooled OLS, Fixed Effects, and Random Effects) is used in this research. The results have shown that leverage, dividend policy and profitability, have a positive and significant impact on firms' value. A rise in these factors will lead to an increasing stock price, whereas even though has has a positive impact, but investment decision not a substantial effect on company value.